Small molecule metalloprotease inhibitor with in vitro, ex vivo and in vivo efficacy against botulinum neurotoxin serotype A. (October 2017) - Jacobson, Alan R.; Adler, Michael; Silvaggi, Nicholas R.; Allen, Karen N.; Smith, Genessa M.; Fredenburg, Ross A.; Stein, Ross L.; Park, Jong-Beak; Feng, Xiaochuan; Shoemaker, Charles B.; Deshpande, Sharad S.; Goodnough, Michael C.; et al.
Abstract: Botulinum neurotoxins (BoNTs) are the most toxic substances known to mankind and are the causative agents of the neuroparalytic disease botulism. Their ease of production and extreme toxicity have caused these neurotoxins to be classified as Tier 1 bioterrorist threat agents and have led to a sustained effort to develop countermeasures to treat intoxication in case of a bioterrorist attack. While timely administration of an approved antitoxin is effective in reducing the severity of botulism, reversing intoxication requires different strategies. In the present study, we evaluated ABS 252 and other mercaptoacetamide small molecule active-site inhibitors of BoNT/A light chain using an integrated multi-assay approach. ABS 252 showed inhibitory activity in enzymatic, cell-based and muscle activity assays, and importantly, produced a marked delay in time-to-death in mice. The results suggest that a multi-assay approach is an effective strategy for discovery of potential BoNT therapeutic candidates. Graphical abstract: Highlights: ABS 143 and ABS 252 inhibited the proteolytic activity of BoNT/A light chain. Inhibition involved specific interactions with active site groups in the light chain. ABS 252 antagonized BoNT/A-mediated cleavage of SNAP-25 in primary neurons. ABS 252 slowed onset of paralysis in BoNT/A-intoxicated nerve-muscle preparations. ABS 252 delayed time-to-death in mice intoxicated by BoNT/A.